A novel locus for autosomal dominant non-syndromic deafness (DFNA41) maps to chromosome 12q24-qter. Issue 8 (1st August 2002) - Blanton, S H; Liang, C Y; Cai, M W; Pandya, A; Du, L L; Landa, B; Mummalanni, S; Li, K S; Chen, Z Y; Qin, X N; Liu, Y F; Balkany, T; et al.
Abstract : We have studied 36 subjects in a large multigenerational Chinese family that is segregating for an autosomal dominant adult onset form of progressive non-syndromic hearing loss. All affected subjects had bilateral sensorineural hearing loss involving all frequencies with some significant gender differences in initial presentation. After excluding linkage to known loci for non-syndromic deafness, we used the Center for Inherited Disease Research (CIDR) to test for 351 polymorphic markers distributed at approximately 10 cM intervals throughout the genome. Analysis of the resulting data provided evidence that the locus designated DFNA41 maps to a 15 cM region on chromosome 12q24.32-qter, proximal to the marker D12S1609. A maximum two point lod score of 6.56 at 𝛉=0.0 was obtained for D12S343. This gene is distal to DFNA25, a previously identified locus for dominant adult onset hearing loss that maps to 12q21-24. Positional/functional candidate genes in this region include frizzled 10, epimorphin, RAN, and ZFOC1 .